Differences in recent and future trends in the Arabian Sea oxygen minimum zone: processes and uncertainties - Lachkar, Zouhair; Lévy, Marina; Hailegeorgis, Derara; Vallivattathillam, Parvathi (Frontiers in Marine Science, 2023)
The Arabian Sea is an exceptionally complex system that hosts a highly productive marine ecosystem. This intense productivity leads to high oxygen consumption at depth that maintains, together with the sluggish circulation, the world’s thickest oxygen minimum zone (OMZ). While observations have been scarce in the region, evidence for a recent (1960-2020) decline in oxygen is emerging in the northern Arabian Sea. However, in the longer term (2050 to 2100) the future evolution of the OMZ is more uncertain, as the model projections that have been carried out are not consistent with each other. On the one hand, this reflects the limitations of current generation models that do not adequately represent key physical and biogeochemical processes, resulting in large O2 biases in the region under present-day conditions. On the other hand, the inherent difficulty of predicting future O2 conditions in the Arabian Sea is a consequence of the sensitivity of O2 supply and consumption to local and remote changes that evolve on different timescales. Here we aim to synthesize current knowledge of the Arabian Sea OMZ in relation to important factors controlling its intensity and review its recent change and potential future evolution. In particular, we explore potential causes of the differences in recent and future O2 trends in the region and identify key challenges to our ability to project future OMZ changes and discuss ideas for the way forward.